From Rage to Resignation: Reading Tina Mabry’s Mississippi Damned as a Post–Civil Rights Response to Nina Simone’s “Mississippi Goddam” - Moore, Marlon Rachquel (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Much has been written about Nina Simone’s song “Mississippi Goddam” because it lyrically achieves the political consciousness of the embattled community whose experiences and energy it intends to speak to, through, and for. With its curse words, impatient tone, and energetic rhythm, it could never be mistaken for the traditional, Christian-inflected civil rights dirge. “Alabama’s got me so upset,” the chorus complains. “Tennessee made me lose my rest, and,” as if its atrocities need not be spelled out, “every body knows about Mississippi, goddam!” The song was banned from radio airplay but still became part of the civil rights sound
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; _Nettoyé

Impossible Presence: Toward a Queer Singapore Cinema, 1990s–2000s - Chan, Kenneth (Queer Singapore : Illiberal Citizenship and Mediated Cultures, 2012)
The writer frames his analysis of Kan Lume and Loo Zihan's feature length film Solos (2007) with a historical overview of the representation of queer sexualities in new Singaporean cinema. This approach also takes in the Penal Code Section 377A, arguing that not only do these repressive laws force queer sexualities to the margins of culture and society, but also that the State's censorship laws are a means by which it can reify ‘the Asian value system's supposed rejection of queerness’.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Introduction: What Is Queer Production Studies/Why Is Queer Production Studies? - Martin Jr., Alfred L. (Journal of Film and Video, 2018)
An introduction is presented in which the editor discusses various reports within the issue on topics including where and how queerness is produced, the use of paratexts to expand and stop queer readings of films, and queers' non-reliance on mainstream media to produce queer stories.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé